Rancang Bangun Pembangkit Listrik Pikohidro Menggunakan Turbin Screw Pada Aliran Danau PCR - Jupri Yanda Zaira; Oloan Rinaldi Naibaho (Politeknik Negeri Padang, 2023)
Picohydro is a power plant that produces 5 kW of power which consists of 3 components, namely air flow, turbine, and generator to convert maximum energy into electrical energy. Picohydro is an alternative power plant as a substitute for fossil fuel power plants (diesel and gasoline). The PCRlake flow has a flow of 0.019 m3/s which can be used as a potential source of energy to generate electricity, where the tools used are screw turbines, V-belt transmission, and DC generators. The results of the design of the screw turbine that are made have a turbine length specification of 1,140.5 mm, an outside diameter of 419.4 mm, an inside diameter of 225 mm, a turbine pitch of 503.2 mm, a number of blade turns 2 pieces, a turbine angle of 26o, a thread angle of 21o, and a head of 0.5 m. For the transmission, there are 2 type A -V belts that connect the turbine rotation to the DC generator rotation. The results obtained that the theoretical power available in the PCR lake flow is 95.01 watts. The average rotation produced by the 1,398 rpm generator is able to stably turn on as many as 6 DC lamps with a total load of 60 watts. By testing the DC lamp load, a total load of 60 watts produces a generator power of 29.14 watts, a screw turbine power of 34.08 watts. By testing using a braking system at turbine rotation it produces a maximum torque of 13.12 Nm with a screw turbine power of 46.70 watts and a turbine mechanical efficiency of 49.16%.